Valuable and vulnerable children in the Hebrew Bible, especially the Elisha cycle - Parker, Julie Faith (Providence, RI Brown Judaic Studies, 2013)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- Part I: Frameworks for Understanding -- Concepts of Children and Childhood -- Learning about Children and Youth in the Hebrew Bible through Language: A Contextual and Linguistic Framework -- Approaching the Elisha Cycle: A Literary and Methodological Framework -- Part II: Analyses of Stories-Children and Elisha -- The Mockers of Bethel (2 Kings 2:23-25) -- The Moabite Prince (2 Kings 3:26-27) -- The Debt-Collateral Children (2 Kings 4:1-7) -- The Shunammite's Son (2 Kings 4:8-37) -- The Israelite Slave Girl (2 Kings 5:1-14) -- The Sons of the Starving Mothers (2 Kings 6:24-31) -- Epilogue: The Boy Restored to Life (2 Kings 8:1-6) -- Conclusions -- Bibliography -- Index of Biblical Passages -- Index of Authors -- Index of Subjects.
Includes bibliographical references and index
Title from PDF title page (viewed on Jan. 8, 2014)
Keywords: Bible -- Criticism, interpretation, etc; Bible; Children in the Bible; RELIGION ; Biblical Studies ; Old Testament; RELIGION ; Judaism ; Sacred Writings; Children in the Bible; Criticism, interpretation, etc